Challenges facing teachers in teaching information communication technology in basic schools: A case study in Komenda Edina Eguafo Abrem Municipality - Addokor, Richard Delali (University of Cape Coast, 2020)
The study was carried out to find the challenges that face teachers in teaching information communication technology in basic schools in Komenda Edina Eguafo Abrem (KEEA) Municipality in the Central Region. A descriptive design was used to determine and report the findings of the study. The study covered six out of twelve public schools in Elmina circuit in KEEA Municipality. In all, 58 teachers were involved in the study. Questionnaires were the main instrument used in the collection of data for the study. Data collected was analyzed using frequencies and percentages. The result of the study shows that the schools do not have adequate ICT tools and equipment necessary for practical lessons. It is also an evident from the study that, most teachers do not have adequate skills to integrate ICT in their teaching and learning processes. It also indicated that most teachers do not have good attitudes towards the use of ICT in the teaching and learning processes and this may be because most teachers do not have requisite skills in handling IT tools and equipment. Moreover, the study shows that majority of the teachers have positive perception in relation to the use of ICT in the classroom. There is the need for the release of funds for purchasing and repairing ICT tools and equipment in basic schools. ICT laboratories should be built for our basic schools to accommodate enough students at time looking at their population size for effective and efficient teaching and learning environment. Finally, periodic conferences, workshops or seminars on ICT in education should be organized for the basic school teachers.
x, 99p:,ill.
Keywords: Information Communication Technology; Challenges; Teachers; Komenda Edina Eguafo Abrem